Determining the total sulfur amino acid to lysine requirement of the lactating sow - Schneider, J.D.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 163 sows were used in a study to determine the requirement for total sulfur amino acids (TSAA), relative to lysine, during lactation. All experimental diets were cornsoybean meal-based and formulated to contain 0.88% true ileal digestible (TID) lysine (0.97% total lysine). The experimental diets contained 0.37% L-lysine HCl, with other crystalline amino acids added to ensure that TSAA was first limiting. The dietary TID TSAA rates were formulated to 0.44, 0.48, 0.53, 0.57, and 0.62%, corresponding to 50, 55, 60, 65, and 70% of lysine, respectively. Sows farrowed in six farrowing groups, and were randomly allotted to the dietary treatments on the basis of parity. Over the entire lactation period, there were no differences (P>0.14) in ADFI, weight loss, backfat loss, or plasma urea nitrogen among sows fed increasing TSAA:Lys ratios. Increasing TSAA, relative to lysine, had no effect (P>0.25) on litter weaning weight or preweaning mortality. In summary, there were no differences in litter performance with increasing TID TSAA:Lys ratio. These results suggest that the requirement for TID TSAA is no more than 50% of lysine. Additional research is needed to confirm this relatively low TSAA requirement, and that the relatively high feed (and amino acid) intake of sows, coupled with possible tissue breakdown as a source of TSAA, did not decrease the dietary requirement.
Keywords: Total sulfur amino acid; Lactation; Sows; Swine